Detection of genetic mutations associated with macrolide resistance of Mycoplasma pneumoniae - Chi Eun Oh; Eun Hwa Choi; Hoan Jong Lee (Korean Pediatric Society, 2010)
Purpose : The aim of this study was to identify mutations associated with macrolide resistance in Mycoplasma pneumoniae (MP) and to establish a cultural method to determine antimicrobial susceptibility. Methods : Nasopharyngeal aspirates (NPAs) were collected from 62 children diagnosed with MP pneumonia by a serologic method or polymerase chain reaction. The 23S rRNA and L4 ribosomal protein genes of MP were amplified and sequenced. To identify mutations in these 2 genes, their nucleotide sequences were compared to those of the reference strain M129. MP cultivation was carried out for 32 (28 frozen and 5 refrigerated) NPAs and M129 strain using Chanock's glucose broth and agar plate in a 5% CO2 incubator at 37?#608;and examined at 2-3 day intervals for 6 weeks. Results : Among the 62 specimens, 17 had M144V mutations in ribosomal protein L4. The A2064G mutation was observed in 1 specimen; its 23S rRNA gene was successfully sequenced. Culture for MP was successful from the M129 strain and 2 of the 5 NPAs that were refrigerated for no longer than 3 days. However, MP did not grow from the 28 NPAs that were kept frozen at -80?#608;since 2003. Conclusion : We found the M144V mutation of L4 protein to be common and that of domain V of 23S rRNA gene was relatively rare among MP. Studies on the prevalence of macrolide-resistant MP and the relationship between the mutations of 23S rRNA gene and ribosomal protein L4 will aid in understanding the mechanism of macrolide resistance in MP.